Neuromuscular, endocrine and perceptual responses during different length between-match microcycley in professional Rugby League players - Coutts, A. J.; McLean, B. D.; Kelly, V.; Cormack, S. J.; McGuigan, M. R. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
Appropriate recovery between matches is critically important in team sports which have regular competition. Reduced neuromuscular performance, alterations in hormone levels and increased perception of fatigue have been reported in rugby league players enduring a mismatch between training stress and recovery [1, 2]. However, the recovery patterns in these variables following professional rugby league matches is unknown. Therefore, the purpose of this study was to examine the time course of change in neuromuscular, perceptual and hormonal measures following a professional rugby league match during different length between-match microcycles. METHODS: Following familiarisation, 12 professional rugby league players from the same team were assessed for changes in countermovement jump (CMJ) (force, power, flight time)[3], perceptual responses (fatigue, well being and muscle soreness) and salivary hormone (testosterone (T) and cortisol(C)) levels during 5, 7 and 9 day between-match training microcycles. Measures were taken 4 h prior to the first match, and then 1, 2, 4, 6*, 7*, 8* and 9* days following (*depending on group). All training was prescribed by the club coaches and was monitored using the session-RPE method. RESULTS: Significantly lower mean daily training load was completed on the 5-day compared with the 7 and 9-day conditions. Some CMJ variables (flight time and contraction time), perception of fatigue, well-being and muscle soreness were significantly reduced in the 2 days following the match in each condition (P<0.05). All CMJ variables returned to near baseline values following 4 days in each condition. Both CMJ maximum and relative power was lower in the 7 day condition when compared with the 9 day condition (P<0.05). Fatigue levels were reduced at 48 h in the 7 and 9-day groups (P<0.05) but had returned to baseline in the 5-day group. All perceptual measures returned to baseline levels prior to the following match in each condition and followed changes in training load. Salivary T and C did not change in response to the match. DISCUSSION: Neuromuscular performance and perception of fatigue are reduced for at least 48 h following a rugby league match but these can be fully recovered within 4 days. CMJ variables involving flight time appear to be best for assessing acute fatigue caused by a match, and variables involving power may be useful in assessing accumulated fatigue. The perceptual measures were sensitive to both acute fatigue and accumulated fatigue. The salivary hormone analyses have limited practical value for assessing recovery. These findings show that with correct training, it is possible to recover neuromuscular, perceptual and endocrine measures within 4 days after a professional rugby league match.